Lead, chromium and cadmium in coloured printing inks used in children's magazines - Low, Kun She; Lee, Chnoong Kheng; Matu Lejau, Marcus Hugo (Universiti Pertanian Malaysia, 1985)
One hundred and five coloured magazines and comics commonly available in the Malaysian market were analysed for lead, chromium and cadmium. A few with high lead content were extracted under simulated stomach conditions. Results were compared with those from the United States, England and Finland.